Growth, survival and reproduction of the Turkish medicinal leech, Hirudo sulukii - Ceylan, Mustafa; Kucukkara, Ramazan; Erbatur, Ismail; Karatas, Emin; Tunc, Meryem; Saglam, Naim (Taylor & Francis Ltd, 2021)
The present study aimed to investigate growth, survival and reproduction of the Turkish medicinal leech, Hirudo sulukii, endemic to Southeastern Anatolia and whose biology is poorly understood. In comparison with the Southern medicinal leech, Hirudo verbana, which has a wide distribution throughout Eurasia, H. sulukii grew faster until the fourth month, then growth increased significantly in favour of H. verbana. At the beginning of gravidity, high mortality occurred in specimens of H. sulukii not transferred to moist peat, the cocoon deposition area. Gravidity occurred in almost all (98%) H. sulukii adults, but was detected in only 60% of H. verbana adults. Unlike the growing period, survival rate was greater in H. sulukii during the reproductive period. Gravidity and cocoon laying periods lasted longer in H. sulukii, which continued reproductive activity even in colder conditions. There were more and smaller sized cocoons having higher deformation rate in H. sulukii. Likewise, fewer and larger offspring having lower morphological abnormality were observed in cocoons having lower hatchling rates in H. sulukii. Collectively, our findings reveal that H. sulukii reaches adult size relatively early, continues its reproduction in cold conditions and displays high reproductive performance, thus making it a strong candidate for leech aquaculture.
Keywords: Endemic; Annelida; Clitellata; mortality; gravidity; cocoon